A Study of the Flow Patterns in the Gas Phase of a Bubbling Column - Hill, Peter (My University, 1964)
The gas phase flow patterns in a bubbling column were investigated, using tracer methods to establish the residence time distributive An analogue computer obtained the moments if this distribution directly. The air flow rate and column height were varied. The results showed that as the air flow rate increased, although the voidage increased, the mean residence tine decreased. Thus an increasing proportion if the gas phase behaved as a stagnant volume. The results are correlated in terms of a mixed region model. Other work showed that an increase of liquid viscosity, or the inhibition of coalescence, affected only the stagnant volume. The rate of coalescence was investigated and an estimate of its magnitude was obtained.
Keywords: flow pattern; gas phase; bubbling column